Comparison of heart rate variability and pulse rate variability detected with photoplethysmography - Rauh, Robert; Limley, Robert; Bauer, Rainer-Dieter; Radespiel-Troger, Martin; Mück-Weymann, Michael (Proceedings Volume 5474, Saratov Fall Meeting 2003: Optical Technologies in Biophysics and Medicine V, 2004)
This study compares ear photoplethysmography (PPG) and electrocardiogram (ECG) in providing accurate heart beat intervals for use in calculations of heart rate variability (HRV, from ECG) or of pulse rate variability (PRV, from PPG) respectively. Simultaneous measurements were taken from 44 healthy subjects at rest during spontaneous breathing and during forced metronomic breathing (6/min). Under both conditions, highly significant (p > 0.001) correlations (1.0 > r > 0.97) were found between all evaluated common HRV and PRV parameters. However, under both conditions the PRV parameters were higher than HRV. In addition, we calculated the limits of agreement according to Bland and Altman between both techniques and found good agreement (< 10% difference) for heart rate and standard deviation of normal-to-normal intervals (SDNN), but only moderate (10-20%) or even insufficient (> 20%) agreement for other standard HRV and PRV parameters. Thus, PRV data seem to be acceptable for screening purposes but, at least at this state of knowledge, not for medical decision making. However, further studies are needed before more certain determination can be mad
Keywords: Photopletysmography; heart rate variability; pulse rate variability; Bland and Altman analysis; physiology